2021
DOI: 10.3390/antiox11010064
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Analgesic Effects of Naringin through Selective Inhibition of Transient Receptor Potential Vanilloid Member 1

Abstract: Transient receptor potential vanilloid member 1 (TRPV1) is activated in response to capsaicin, protons, temperature, and free reactive oxygen species (ROS) released from inflammatory molecules after exposure to harmful stimuli. The expression level of TRPV1 is elevated in the dorsal root ganglion, and its activation through capsaicin and ROS mediates neuropathic pain in mice. Its expression is high in peripheral and central nervous systems. Although pain is a response evolved for survival, many studies have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…The rich profile of flavonoids found in camelina DSM contains high levels of vitexin and naringenin, which account together for more than 99% of total flavonoids. Both vitexin and naringenin were considered in the recent literature for their neuroprotective effects and inhibition of inflammatory and neuropathic pain [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rich profile of flavonoids found in camelina DSM contains high levels of vitexin and naringenin, which account together for more than 99% of total flavonoids. Both vitexin and naringenin were considered in the recent literature for their neuroprotective effects and inhibition of inflammatory and neuropathic pain [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…We observed that pre-treating the animals with the selective PPAR-α receptor antagonist GW6471 almost completely prevented the acute pain-relief offered by camelina administration in DNBS animals. The effect was independent of the activation of PPAR-Ƴ receptor or the CB1 and CB2 receptors, which are involved in pain regulation as well [ 43 , 49 , 50 , 67 , 68 ]. Interestingly, PPAR-α is involved in the modulation of pain signalling [ 69 ], as well as in several pathophysiological mechanisms, some of which contribute to pain development such as neuroinflammation and oxidative stress [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various flavonoids induced TRPV1-mediated antinociceptive effects, such as reduction in carrageenan-, capsaicin- and chronic complete Freund’s adjuvant (CFA)-induced mechanical and thermal hyperalgesia [ 164 , 165 , 166 , 167 ]. Flavonoids with TRPV1 antagonistic properties included various compounds: naringenin [ 168 ], cochinchinemin A and B, loureirin B [ 169 ], gomisin A [ 170 ], eriodictyol [ 165 ], quercetin [ 171 ] and vitexin [ 164 ].…”
Section: Natural Modulators Of Trpv1 Channelmentioning
confidence: 99%
“…Eom et al showed that naringin acted in a concentration-dependent and voltageinsensitive manner, reversibly inhibited the interaction with transient receptor potential cation channel subfamily V member 1 at the cellular and molecular levels, and had an IC 50 value of 33.33 µM. Naringin only inhibited inward peak current without affecting inward peak current [15]. They cross-checked the results from TEVC and docking experiments and found that D471 and N628 of transient receptor potential cation channel subfamily V member 1 were involved in binding with naringin.…”
mentioning
confidence: 99%